(±)-Camphor-10-sulfonic acid as recyclable and efficient catalyst for the synthesis of some novel coumarin derivatives. Issue 1 (2nd January 2016) - Kumbhar, Digambar; Patil, Reshma; Patil, Dayanand; Patravale, Ajinkya; Chandam, Dattatray; Jadhav, Sunetra; Deshmukh, Madhukar
ABSTRACT: A highly competent-diversity oriented synthesis of coumarin core derivatives using a Knoevenagel condensation followed by Michael addition and subsequent cyclization in the presence of (±)-camphor-10-sulfonic acid in a water/ethanol (1:1) solvent system is depicted. Furthermore, easy workup procedures with good yield, rapid reactions with high atom economy, and catalyst recyclability are the fascinating features of the procedure. GRAPHICAL ABSTRACT: